BASIC CLASSIFICATION SYSTEMS FEATURES AS A TOOL FOR MANAGEMENT AND INVESTMENT ANALYSIS OF SUBSOIL USE PROJECTS - LYTVYNYUK, Stanislav; KURYLO, Mariia; VIRSHILO, Ivan; BRATAKH, Mykhailo (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
First classification systems of mineral reserves and resources appeared in the beginning of the 20th century, which coincided with the mining development in the UK, Germany and the USA. Modern classifications of mineral raw materials and energy resources, their terminology, definitions and concepts have been developed and improved for more than 40 years. Separate development of the most commonly used classifications has led to the emergence of various definitions and determinations of characteristics of the same or similar categories of mineral reserves and resources according to geological and technical-economic characteristics. The article proposes methodological approaches of "operational harmonization" (universal classifier) as a toolkit for resource management and investment analysis of deposits (subsoil areas) of solid (metallic and non-metallic) minerals. The analysis and classification of the resources of the complex subsoil use project, which includes the use of geothermal resources, salt reserves, and the accompanying extraction of useful components from the associated reservoir waters, which differ in the degree of study and implementation, have been carried out. For this Solotvino project, full consideration of all classification features of both individual component resources and the project as a whole is recorded, only when applying the UNFC classification.